Self-Understanding of a Woman in the Prose of the Emigrants - Račiūnaitė, Vaiva (Sociologija. Mintis ir veiksmas, 1998)
The article aims to analyze the woman's self-understanding in the prose of Lithuanian emigrants in the interwar years. The author of the article suggests to discuss the self-understanding as a conflict between two cultures - the modern and the traditional, whose conflict becomes evident with the increasing role of the city in the everyday life. The crisis of patriarchal culture that becomes evident with the diminishment rural communities provides the grounds to discuss the specifics of woman's self-understanding in the Lithuanian prose of the first half of the twentieth century.
Keywords: woman's self-understanding; Lithuanian prose; city and rural community; modern and traditional culture